(untitled) (International Journal of Innovative Research in Computer Science & Technology, 2022)
Electricity is required in every country and state, so if the electricity is required, then a consistent and good as well as dependable electricity supply is required. ML is becoming growing and vast in the every fields of the work, such as electrical powers system, electronic parts, work software’s and tools, and construction. Artificial intelligence (AI) is becoming increasingly important in everyday life, including home and business automation. The amount of research being done on the power system is growing years by years, and today AI is being used to make power systems smarter. Power systems are based on geography, weather, or any specific area. Other factors that the power system is reliant on include the introduction of new technologies, the upgrading and modification of technology and equipment, energy transmission, and distribution. AI stands for artificial intelligence, which is a sophisticated approach for assessing and solving any problem. As a result, it may be used to address a variety of issues that arise in power systems, such as control, planning, scheduling, and prediction. The scope of AI for power systems as well as the use of AI in handling intricate electrical connections were discussed in this article.